Consumer confusion in healthcare decision-making and choice: a qualitative exploration of patient confusion. Issue 3 (3rd July 2021) - Chauhan, Vishakha; Sagar, Mahim
ABSTRACT: Owing to the importance of understanding consumer confusion in the complexities of healthcare decision-making and choice, this study aims to conceptualize the patient confusion phenomenon. In this specific context, the adaptive decision-making model was used as a theoretical paradigm for understanding factors affecting the phenomenon. A qualitative approach was used to collect data from 22 patients regarding their confusion experiences during healthcare decision-making. Phenomenological analysis of the interview transcripts reflected factors belonging to three core themes affecting patient confusion, namely, the characteristics of the decision maker, the characteristics of the decision problem, and the embeddedness in the social context.